Transgenic pigs carrying cDNA copies encoding the murine Mx1 protein which confers resistance to influenza virus infection - Müller, M; Brenig, B; Winnacker, E L; Brem, G (Gene, 1992)
An important aspect of gene transfer into farm animals is the improvement of disease resistance. The mouse Mx1 protein is known to be sufficient to confer resistance to influenza viruses. Gene constructs containing the mouse Mx1 cDNA controlled by the human metallothionein IIA promoter (hMTIIA::Mx), the SV40 early enhancer/promoter region (SV40::Mx) and the mouse Mx1 promoter (mMx::Mx) were transferred into pigs. The results of the gene transfer experiments with the hMTIIA::Mx and the SV40::Mx constructs indicate that the permanent high-level synthesis of Mx1 might be deleterious to the organism: the gene transfer efficiency was surprisingly low, and all transgenic piglets born had rearrangements in their transgene copies that abolished protein synthesis. The use of the interferon (IFN)- and virus-inducible mMx::Mx construct resulted in normal gene transfer efficiency. Two transgenic pig lines could be established which expressed IFN-inducible mouse Mx1 mRNA. Extensive protein analysis did not detect mouse Mx1 in IFN-treated transgenic animals.